Effect of spacing and nitrogen levels on performance of hybrid napier in semiarid ecosystem of Gujarat - KHADDA, B S; LATA, KANAK; KUMAR, RAJ; RAI, A K; JADAV, J K (The Indian Journal of Agricultural Sciences, 2016)
The present study was undertaken during 2011-12 at Krishi Vigyan Kendra, Panchmahal to find out the effect of spacing and nitrogen levels on performance of hybrid napier in semi-arid ecosystem of Gujarat. The results revealed that the different spacing could not exert significant effect on the plant height, whereas nitrogen levels significantly influenced the plant height. The application of higher dose of nitrogen (200 kg/hr) significantly exhibited higher plant (132.25 cm) followed by 175 and 150 kg/ha N. Tillers/clump and leaf stem ratio was influenced significantly owing to different spacing and levels of nitrogen. The highest leaf stem ratio and more number of leaves/stem were recorded with the spacing of 75 cm × 60 cm and application of 200 kg/ha. The green fodder yield was increased significantly with increasing the spacing and levels of nitrogen. Interaction effect of adoption of spacing and levels of nitrogen indicate that the treatment combination having spacing 75 cm × 60 cm and nitrogen level 200 kg/ha recorded significantly highest green fodder yield. Higher gross returns, net return with maximum benefit cost ratio were recorded when the clumps were planted at the spacing 75 cm × 60 cm with of 200 kg/ha N.